Strangers and Fellow Citizens: Perspectives on Immigration and Society - Wabel, Thomas (Studies in Christian ethics, 2021)
The article sets out a critical assessment of recent public reactions in Germany upon taking in large numbers of refugees since 2015, which have been swaying between moralisation and resentment. In this situation, public theology should ask how hospitality is linked to the perceived identity of a society and to its perception of who belongs, and what role Christianity might play in these debates. Drawing on a phenomenological perspective within contemporary German philosophy (Bernhard Waldenfels), and contrasting this perspective with historical and contemporary voices on migration within political philosophy (Georg Simmel, Michael Walzer), the article explores what the concepts of stranger, member and guest imply for the relation of ‘us’ to ‘the other’. From this, I derive a suggestion as to how Christian theology could contribute to a change in the self-perception of society, centred around the seemingly paradoxical concept of ‘belonging in not-belonging’.